2014
DOI: 10.3390/ani4020146
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Biological Processes to Eliminate Antibiotics in Livestock Manure: An Overview

Abstract: Simple SummaryBeside their use to treat infections, antibiotics are used excessively as growth promoting factors in livestock industry. Animals discharge in their feces and urine between 70%–90% of the antibiotic administrated unchanged or in active metabolites. Because livestock manure is re-applied to land as a fertilizer, concerns are growing over spread of antibiotics in water and soil. Development of antibiotic resistant bacteria is a major risk. This paper reviewed the potential of anaerobic digestion to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(145 citation statements)
references
References 78 publications
3
126
1
6
Order By: Relevance
“…Following the German recommendations for the best practice for manure applications to low and moderately fertile soils, it was assumed that a maximum of 10 m 3 of manure was applied per hectare. SDZ concentrations can be related to the dry matter content of manure with 51 mg SDZ per kg dry matter (Guo et al, 2012;Massé et al, 2014). Since manure may contain 10 to 20% of dry matter, a dry matter content of 20% was selected as the worst case scenario, resulting in a total SDZ concentration of 10.2 mg/m 2 per manure application.…”
Section: Scenario Simulations: the Long-term Sdz/manure Field Applicamentioning
confidence: 99%
“…Following the German recommendations for the best practice for manure applications to low and moderately fertile soils, it was assumed that a maximum of 10 m 3 of manure was applied per hectare. SDZ concentrations can be related to the dry matter content of manure with 51 mg SDZ per kg dry matter (Guo et al, 2012;Massé et al, 2014). Since manure may contain 10 to 20% of dry matter, a dry matter content of 20% was selected as the worst case scenario, resulting in a total SDZ concentration of 10.2 mg/m 2 per manure application.…”
Section: Scenario Simulations: the Long-term Sdz/manure Field Applicamentioning
confidence: 99%
“…The formation of estrogenic byproducts is consistently observed even in the anaerobic digestion of other materials than sludge (e.g. animal manure) [110][111][112].…”
Section: Anaerobic Digestionmentioning
confidence: 95%
“…Notably, there is similarity in the TrOC removal of composts of different materials, e.g. sludge, manure, and municipal solid waste [40,112,131]. For example, the removal of fluoroquinolones and sulfonamides from sludge (e.g.…”
Section: Compostingmentioning
confidence: 99%
“…The highest and most frequently reported concentrations of antibiotic residues in manure belong to the tetracycline group of antibiotics. The reported levels regularly exceed 100 mg kg-1 (Massé, 2014), with extremes up to 764 mg kg-1 chlorotetracycline in swine manure (Pan, 2011). Observed concentrations for sulfonamides are also considerable: Martinez-Carballo (2007) reported concentrations level up to 20 mg kg-1 for sulfadimidine and up to 91 mg kg-1 for sulfadiazine (Martinez-Carballo, 2007).…”
Section: Antibiotic Resistance In Food Of Animal Originmentioning
confidence: 99%
“…For example, a study by showed that composting reduced the concentration of extractable tetracyclines, sulfonamides and macrolides with 96%, 99% and 95%, respectively. Anaerobic digestion has also been suggested as an effective method to degrade and remove antibiotics (Massé, 2014). The removal of antibiotics during such processes is mainly attributed to temperature dependent abiotic processes such as adsorption and degradation (Aust, 2008;Arikan, 2009).…”
Section: Degradation (Transformation)mentioning
confidence: 99%